Die Mehrsprachigkeit als Herausforderung und Chance bei der Auslegung des Unionsrechts. Praktische Anmerkungen aus der Perspektive des Kabinetts einer Generalanwältin - Sobotta, Christoph (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2015)
This contribution aims at highlighting the multiple challenges and opportunities that result from the multilingual nature of EU law. Although its nature in principle requires that all language versions of EU provisions are taken into account when interpreting EU law, such an approach implies substantial practical difficulties. Nevertheless, in case of doubt, this method should be used to properly identify the whole interpretative potential of a provision. Once identified, this potential needs to be narrowed down by using the classical interpretative methods. While dealing with the various language versions falls within grammatical interpretation, historical, systematical and teleological interpretation may help to clarify which language versions properly reflect the intention of the legislator, fit within the legal context and achieve the objective of the rules at stake. For the future, adequate tools easing the comparison of language versions and the spotting of linguistic discrepancies could be developed. The author is a Legal Secretary in the Cabinet of Advocate General Juliane Kokott. His contribution only reflects personal views. It is based on a conference he gave at the Verein zur Förderung der Europäischen Rechtslinguistik (Association for promoting European Legal Linguistics) in Cologne on 16 May 2014. The author thanks Wolfgang Rosch, Nina Neumann and Tilman Reinhard for their valuable comments and suggestions.